Investigating the PS seismic imaging of faults using seismic modelling and data from the Snøhvit field, Barents Sea - Jennifer Cunningham; Wiktor W. Weiball; Nestor Cardozo; David Iacopini (2021)
Supplementary Material 3. Videos of the unprocessed seismic wave simulation for two HW sources (-7000 m and -2000), a central source (0 m), and two FW sources (+2000m and +7000 m). The videos are available for both vertical (Vz) and horizontal (Vx) particle velocities.